CD2-positive B-cell precursor acute lymphoblastic leukemia with an early switch to the monocytic lineage - Slamova, L; Starkova, J; Fronkova, E; Zaliova, M; Reznickova, L; van Delft, F W; Vodickova, E; Volejnikova, J; Zemanova, Z; Polgarova, K; Cario, G; Figueroa, M; et al. (Leukemia, 2014)
Switches from the lymphoid to myeloid lineage during B-cell precursor acute lymphoblastic leukemia (BCP-ALL) treatment are considered rare and thus far have been detected in MLL-rearranged leukemia. Here, we describe a novel BCP-ALL subset, switching BCP-ALL or swALL, which demonstrated monocytosis early during treatment. Despite their monocytic phenotype, 'monocytoids' share immunoreceptor gene rearrangements with leukemic B lymphoblasts. All swALLs demonstrated BCP-ALL with CD2 positivity and no MLL alterations, and the proportion of swALLs cases among BCP-ALLs was unexpectedly high (4%). The upregulation of CEBPα and demethylation of the CEBPA gene were significant in blasts at diagnosis, prior to the time when most of the switching occurs. Intermediate stages between CD14(neg)CD19(pos)CD34(pos) B lymphoblasts and CD14(pos)CD19(neg)CD34(neg) 'monocytoids' were detected, and changes in the expression of PAX5, PU1, M-CSFR, GM-CSFR and other genes accompanied the switch. Alterations in the Ikaros and ERG genes were more frequent in swALL patients; however, both were altered in only a minority of swALLs. Moreover, switching could be recapitulated in vitro and in mouse xenografts. Although children with swALL respond slowly to initial therapy, risk-based ALL therapy appears the treatment of choice for swALL. SwALL shows that transdifferentiating into monocytic lineage is specifically associated with CEBPα changes and CD2 expression.
Keywords: Neoplasm, Residual; Male; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; kohortové studie; Child, Preschool; pre-B-buněčná leukemie; antigeny CD2; Cohort Studies; Cell Lineage; Adolescent; prognóza; monocyty; Child; Multiplex Polymerase Chain Reaction; dítě; mužské pohlaví; buněčný rodokmen; mladiství; předškolní dítě; multiplexová polymerázová řetězová reakce; lidé; ženské pohlaví; Immunophenotyping; Humans; reziduální nádor; Monocytes; Prognosis; CD2 Antigens; Female; imunofenotypizace